THE STRUCTURE OF HAPPINESS REPRESENTATION FOR RUSSIAN AND AMERICAN REPRESENTATIVES - S. Yu. Zhdanova; A. V. Pecherkina; A. A. Strokanov (Образование и наука)
Introduction. Emotional state of students exerts direct impact on their ability and readiness to cope with challenges when studying, gives rise to the success of educational process and its effectiveness. In this regard, the search of methods and determination of the tasks of psychological diagnostics is brought into focus. Above all, the teacher should consider mentality and valuable attitudes of representatives of various cultures, including their understanding of happiness and personal well-being in the activity against the background of the increasing scales of the international and interethnic mobility.The development of Russian psychology has recently acquired the direction of positive psychology, the focus of which is happiness and positive functioning of the individual. Modern research reveals significant differences in the indicators of happiness and satisfaction with life between representatives of different cultures. However, the diagnostic tools used in such studies are based primarily on the model of happiness image that has been developed in American psychology. In this connection, the question arises as to what extent the image of happiness in American culture correlates with the image of happiness in Russian culture.The aim of this work is to study the representation of happiness between representatives of American and Russian culture, the definition of invariable and variable components in the structure of representation.Methodology and research methods. The study included several stages. At the first stage, the theoretical analysis and development of the ontology of the subject area “Psychology of Happiness” was carried out. At the second stage, an empirical study of the representations of American and Russian respondents was carried out. The main method of data collection was a narrative interview; a method of early personal memories was used to obtain the narrative of happiness. Subsequent processing of verbal characteristics was carried out using segmental content analysis. The K. Muller’s technique of sign analyzing was used for nonverbal characteristics. Statistical analysis of the data was based on the use of the coefficient of φ-angular Fisher transform, correlation coefficient φ, and cluster analysis.Results and scientific novelty. Three multimodal clusters were selected, the structure of each included verbal and non-verbal characteristics of the oral narrative of happiness, individual characteristics (gender, age), and personality traits (extraversion-introversion). It is shown that these clusters are invariant and are manifested in the representation of the state of happiness, regardless of belonging to culture. The variability in the oral narrative of happiness is manifested in the differences in the frequency of access to the categories represented in the clusters identified, as well as in minor changes in the structure of clusters due to age. In particular, the Russian students more often appealed to the categories describing values of family and family well-being, as well as they used the non-verbal units showing aspiration to deduction of emotional state. The American students were more inclined to the choice of the verbal units connected with achievements in activity, and non-verbal categories (peripheral gestures) indicating importance of the relations with other people. The verbal and non-verbal units, reflecting interaction with a social context, have been equally presented in the sample of the Russian and American respondents’ representations.Practical significance. The materials of the present publication can be taken into account when choosing methods of work in the framework of positive psychotherapy, as well as in developing training programs aimed at raising the level of subjective well-being, happiness and satisfaction with life. The obtained results are the basis for the development of practical recommendations for improving the effectiveness of intercultural communication, the security of interpersonal interaction. The experience of using the method of analyzing the sign units can be the basis for developing an automated system for analyzing the emotional state of an individual based on video fragments.